Pengembangan Strategi Pembelajaran Dalam Proses Pembelajaran Pendidikan Agama Islam - Arman, Dedi (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2023)
The aim of this study is to analyze the importance of PAI learning, the challenges faced in the learning process, and the relevance of the development of learning strategies in the context of Islamic education. The method applied in this research is the method of library research with steps: identifying research topics, identifying keywords, searching for literature, scrutinizing literature, analyzing literacy, writing literature summaries, and drawing conclusions. As a result, the importance of PAI learning in the context of education is not only limited to theological understanding but also covers important aspects in the formation of Muslim individuals who are characteristic and contribute positively to society. As for the challenges in the learning process: less relevant use of technology, integration of Islamic values in less-favorable lives, and less conducive learning environments. While the relevance of strategic analysis in the PAI learning process can increase student learning interest and material understanding, as well as the presence of positive changes in student behavior and attitudes, The hope is that this research can make a significant contribution to the development of more effective learning strategies in PAI learning.